Food Situation of living at Home with Dementia and their Care-takers - Sieber, Gabrielle; Kolb, Christian; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

Nutrition at Home: A Challenge for People with Dementia and Family care-takers - Sieber, Gabrielle; Kolb, Christian; Sieber, Cornel; Remmers, H.; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

nutritionDay in the Nursing Home: What is unfavourable for the Prognosis- a low BMI or Weight Loss? - Wirth, R.; Smoliner, C.; Kolb, Christian; Hiesmayr, M.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2014)

The impact of weight loss and low BMI on mortality of nursing home residents - Results from the nutritionDay in nursing homes - Wirth, Rainer; Streicher, Melanie; Smoliner, Christine; Kolb, Christian; Hiesmayr, Michael; Thiem, Ulrich; Sieber, Cornel; Volkert, Dorothee (Clinical Nutrition, 2016)
Weight loss and low body-mass-index (BMI) are well-known risk factors for mortality among older persons. Both items represent a reduced nutritional state but their nature is different. It is, however, unclear which of these factors is more important for prognosis and if there is interference or interaction between them.To measure the prevalence of low BMI and weight loss in nursing home residents and to analyze their impact on mortality.The nutritionDay in nursing homes is an international annual one-day cross sectional survey evaluating malnutrition and 6-months mortality. The data collected from 2007 to 2012 were analyzed. The mortality risk due to a BMI <20 kg/m(2) and weight loss >5 kg was calculated by logistic regression analysis with adjustment for confounding factors.In total, 10,298 residents with a mean age of 85 years (78% female) from 191 nursing homes in 13 countries were included in the analysis. Eighteen percent (17.7%) had a low BMI < 20 kg/m(2), and 11.3% lost > 5 kg of body weight in the previous year. Low BMI <20 kg/m(2) and weight loss >5 kg were both independent and significant risk factors for 6-months mortality (OR 1.7 and 1.5; p < 0.001 in the adjusted model). In comparison to the effect size of low BMI and weight loss alone, the interaction of both factors was substantial (OR = 1.4; p = 0.056). The average 6-months mortality was 13.8%. Subjects with BMI >=20 kg/m(2) without weight loss >5 kg presented the lowest mortality of 11.2%. In subjects with one of the two features, weight loss >5 kg or low BMI <20 kg/m(2), mortality was significantly increased to 17.4% and 19.8%, respectively. However, if both features were present simultaneously the mortality increased disproportionally to 35.7% (OR 3.5; p < 0.001). In addition, this study presents an overlap and a strong dose-effect relationship of both items with regard to the 6-month mortality.A BMI <20 kg/m(2) and weight loss >5 kg in one year are both independent and equally relevant risk factors for the 6-months mortality of nursing home residents aged 65 years or older. For this reason weight loss should be avoided and residents with a low BMI and weight loss should receive particular attention and nutritional care.
EVALuna2:10598

The "nutrition Day in Nursing Homes" - large Heterogeneity between the Institutions and Occupancy of various Participating Countries - Luzsa, R.; Volkert, Dorothee; Kolb, Christian; Mouhieddine, M.; Kosak, S.; Schindler, K.; Hiesmayr, M.; Sieber, Cornel; Diekmann, Rebecca (Zeitschrift für Gerontologie und Geriatrie, 2013)

The nutritionDay in the Nursing Home 2007-2012-Old Age and Nutritional Status - Diekmann, Rebecca; Luzsa, Robert; Kolb, Christian; Mouhieddine, M.; Kosak, S.; Schindler, K.; Hiesmayr, M.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

We cannot care alone. Volunteers in dementia care at Nurnberg General Hospital - Eggenberger, E.; Myllymaeki, J.; Kolb, Christian; Martschin, R.; Bollheimer, L. C.; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2013)
People with dementia have specific care needs especially in an acute care setting. Professionals in clinical routine have limited capacities in meeting the needs of dementia patients as far as communication, interaction and orientation are concerned.For 2 years, the Department of Internal Medicine and Geriatrics at Nurnberg General Hospital has hosted volunteers in dementia care who accompany and visit people with dementia during their acute care stay. We present the organization of the volunteer training program, training content, and preliminary evaluation results.We chose a mixed methods approach for research and evaluation. Baseline data, motivational profile of volunteers, paper and pencil data on attitudes, skills and knowledge before and after training were assessed.Preliminary results show a positive effect on attitudes, skills, and knowledge after volunteer training. Volunteers and professionals need continual support and education to enable volunteers to act as an integrative part of the acute geriatric care team.The admission to an acute care setting is often frightening and confusing for dementia patients. Trained volunteers have the potential to make the hospital stay more pleasant for people with dementia.
Keywords: Hospital volunteers; General hospitals; Geriatric nursing; Training; Quality of health care